Do Oil Price Shocks Matter for Environmental Degradation? Evidence of the Environmental Kuznets Curve in GCC Countries - Ebaid, Ali; Lean, Hooi Hooi; Al-Mulali, Usama (Frontiers in Environmental Science, 2022)
This paper aims to examine the asymmetric impact of oil price shocks on environmental degradation for a panel of six Gulf Cooperation Council (GCC) countries from 1996 to 2016. We use dynamic seemingly unrelated regressions (DSUR) approach that considers cross-sectional dependency to reveal the interrelations between oil price shocks and carbon dioxide (CO2) emissions. The finding shows that the positive shocks of oil prices have a statistically significant negative effect on CO2 emissions, while negative shocks of oil prices did not affect CO2 emissions. More specifically, the positive oil price shocks have negatively influenced the CO2 emissions in Oman, Bahrain, Saudi Arabia, Qatar, and United Emirates Arab. In turn, the most negative effect is found in Qatar and Saudi Arabia. Meanwhile, the negative shocks of oil prices have statistically significant effects on the CO2 emission of Oman and Saudi Arabia. While for other countries, it does not have a significant impact. Also, the results support an environmental Kuznets curve in Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates; in contrast, the hypothesis was rejected in Bahrain and Oman. This study could help policymakers adopt renewable energy policies and use energy-saving technologies to sustain economic development and improve environmental quality.